Metode Penyelesaian Sengketa Batas Desa UPT Tambak Sari Kecamatan Poto Tano Kabupaten Sumbawa Barat - Rasyid Ridha; Agus Kurniawan; Febrita Susanti; Sri Apriani Puji Lestari (Universitas Muhammadiyah Mataram, 2019)
UPT Tambak Sari is one of the expansion villages in the sub- district of Poto Tano, which has problems against village boundary disputes with surrounding villages, thus inhibiting the process of setting the village boundary to be definitive, therefore it is necessary to Settlement of the village boundary UPT Tambak Sari. The purpose of this research is to know the process of implementing and resolving boundary disputes for UPT Tambak Sari village. The method used is a qualitative description through participatory mapping approach es as well as referring to the Indonesian Ministry of Home Affairs Regulation No. 45 2016 of village boundaries determination and affirmation guidelines. The results obtained from this research is the implementation of the boundary of village boundaries conducted in the internal Cartometris village, and then carried out the boundary settlement deliberation between villages with the exposure of Toponimi and village boundary segments, but weak Regulations and information sources relating to indicative village boundaries precipitate the boundary disputes between villages. In the village boundary determination process has also been agreed on the mechanisms of dispute the village boundary, the mechanism that agreed is the report of the village boundary dispute to the dispute resolution team was then carried out mediation and Deliberation, if there is no agreement then will be in the process of adjudication, in this process of dispute settlement of the village boundary UPT add Sari can be resolved at the mediation level based on the joint decision of the District regent of Sumbawa The history of village formation and regulation.